Cardiac transplantation in children with Noonan syndrome. (1st July 2019) - McCallen, Leslie M.; Ameduri, Rebecca K.; Denfield, Susan W.; Dodd, Debra A.; Everitt, Melanie D.; Johnson, Jonathan N.; Lee, Teresa M.; Lin, Angela E.; Lohr, Jamie L.; May, Lindsay J.; Pierpont, Mary Ella; Stevenson, David A.; et al.
Abstract: NS and related RAS/MAPK pathway (RASopathy) disorders are the leading genetic cause of HCM presenting in infancy. HCM is a major cause of morbidity and mortality in children with Noonan spectrum disorders, especially in the first year of life. Previously, there have been only isolated reports of heart transplantation as a treatment for heart failure in NS. We report on 18 patients with NS disorders who underwent heart transplantation at seven US pediatric heart transplant centers. All patients carried a NS diagnosis: 15 were diagnosed with NS and three with NSML. Sixteen of eighteen patients had comprehensive molecular genetic testing for RAS pathway mutations, with 15 having confirmed pathogenic mutations in PTPN11, RAF1, and RIT1 genes. Medical aspects of transplantation are reported as well as NS‐specific medical issues. Twelve of eighteen patients described in this series were surviving at the time of data collection. Three patients died following transplantation prior to discharge from the hospital, and another three died post‐discharge. Heart transplantation in NS may be a more frequent occurrence than is evident from the literature or registry data. A mortality rate of 33% is consistent with previous reports of patients with HCM transplanted in infancy and early childhood. Specific considerations may be important in evaluation of this population for heart transplant, including a potentially increased risk for malignancies as well as lymphatic, bleeding, and coagulopathy complications.